CNS imaging studies in cystic fibrosis patients presenting with sudden neurological events. Issue 1 (9th August 2019) - Ellis, Samantha; Rang, Catherine; Kotsimbos, Tom; Keating, Dominic; Finlayson, Felicity; Stark, Richard; Thyagarajan, Dominic; Wilson, John
Abstract : Background: Acute neurological events may present as an extrapulmonary complication in patients with cystic fibrosis (CF). These events can be secondary to a range of different aetiologies. Methods: A retrospective analysis of 476 medical records of CF patients attending a large teaching hospital between 2000 and 2018 was performed. Patients presenting with acute neurological events who had MRI brain imaging were evaluated. Patients who had headaches without associated neurological symptoms were excluded from this analysis. Results: Acute neurological presentations, excluding headaches without associated neurological symptoms, were reported in 27 index patients out of the 476 patients. Of these, 16 patients had MRI brain imaging for review. Three patients suffered pathology secondary to vascular events, both ischaemic and haemorrhagic; four patients had evidence of ischaemia or infarction not consistent with a vascular territory stroke and the remaining patients experienced a range of different neurological events. The most common presentation among these patients was seizure activity, followed by a transient motor or sensory deficit. Conclusions: Neurological complications are recognised among individuals with CF. Although rare, they can be secondary to a range of different aetiologies, including dysfunctional cell energetics. Additional studies are required to further evaluate this association.